ENHANCING HUMAN-COMPUTER INTERACTION EDUCATION THROUGH INTERACTIVE LEARNING TOOL: A CASE STUDY ON FITTS’S LAW - Dianita, Orchida; Trapsilawati, Fitri (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2026)
This paper presents the development and evaluation of an interactive educational tool designed to teach Fitts's Law in a Human-Computer Interaction (HCI) course for undergraduate engineering students. The Fitts' Law experiment tool allows students to modify target amplitude (A) and width (W) and observe the resulting Index of Difficulty (ID), Movement Time (MT), and model fitting, including the R-squared (R²) values through the additional plotting tool. Through this student-centered approach, students engage actively with the core concepts of motor behavior and information theory in user interface design. Findings suggest an improvement in students' output through the evaluation of their performance, engagement, conceptual understanding, data literacy and model interpretation, and reflection and perceived learning. The majority of students' remarks over 4 out of 5 maximum scores for all category's performance indicates the effectiveness of interactive learning material in HCI content to strengthen students' understanding and comprehension. This work positions interactive simulation as a necessary approach to overcome challenges in global HCI education by enhancing practical understanding of foundational models.